Poster Presentations 2021
DOI: 10.1136/sextrans-2021-sti.314
|View full text |Cite
|
Sign up to set email alerts
|

P229 Prevalence of macrolide and tetracycline resistant Treponema pallidum strains in syphilis cases, Lima and Pucallpa, Peru

Abstract: likely to use a condom than those in CNB (14.1% vs 5.5%, [age adjusted] AOR=0.32, 95%CI:0.18-0.56). In URB, condom use was associated with being male (16.7% vs 12.2% female, [age/region adjusted] AOR=1.47, 95%CI:1.12-1.94) and weakly associated with being older (16.5% among 17-19y vs 12.9% among 14-16y, AOR=1.27, 95% CI: 0.97-1.68, p=0.08). In CNB, condom use was associated with being female (10.5% vs 1.7% male, AOR=0.16, 95% CI: 0.04-0.58). Among URB participants, condom use was associated with sexual activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study on 25 positive T. pallidum DNA samples from active-syphilis patients found an 88% frequency of macrolide-resistance mutations, but no resistance to tetracyclines, suggesting that macrolides should be avoided in syphilis guidelines [ 75 ]. Additionally, a 2020 study comprising 146 French patients with early syphilis found an 85% resistance to macrolides, but no point mutations for doxycycline resistance and proved the absence of genomic resistance to tetracyclines [ 76 ].…”
Section: Treatment Guidelines and Resistant Pathogensmentioning
confidence: 99%
“…A recent study on 25 positive T. pallidum DNA samples from active-syphilis patients found an 88% frequency of macrolide-resistance mutations, but no resistance to tetracyclines, suggesting that macrolides should be avoided in syphilis guidelines [ 75 ]. Additionally, a 2020 study comprising 146 French patients with early syphilis found an 85% resistance to macrolides, but no point mutations for doxycycline resistance and proved the absence of genomic resistance to tetracyclines [ 76 ].…”
Section: Treatment Guidelines and Resistant Pathogensmentioning
confidence: 99%